All-Small-Molecule Organic Solar Cells Based on a Fluorinated Small Molecule Donor With High Open-Circuit Voltage of 1.07 V - Liu, Chunyan; Qiu, Nailiang; Sun, Yanna; Ke, Xin; Zhang, Hongtao; Li, Chenxi; Wan, Xiangjian; Chen, Yongsheng (Frontiers in Chemistry, 2020)
A new acceptor-donor-acceptor (A-D-A) type small molecular donor, namely DRTB-FT, has been designed and synthesized for all-small-molecule organic solar cells (ASM-OSCs). By introducing fluorine atoms on the thienyl substituent of the central benzodithiophene unit, DRTB-FT shows a low-lying highest occupied molecular orbital (HOMO) energy level of -5.64 eV. Blending with an A-D-A type acceptor F-2Cl, DRTB-FT based ASM-OSCs gave a power conversion efficiency (PCE) of 7.66% with a high open-circuit voltage (Voc) of 1.07 V and a low energy loss of 0.47 eV. The results indicate that high Voc of ASM-OSC devices can be obtained through careful donor molecular optimization.